Micro-level Evidence on the Survival of German Manufacturing Industries - A Multidimensional Analysis - Yvonne Schindele; Michael Fritsch; Florian Noseleit (European Regional Science Association (ERSA), 2010)
Several empirical studies showed that it is not the level of entrepreneurial activity itself, but the (long-term) survival and growth of new firms that determine the direct and indirect contribution of new businesses to regional employment. To this end, the aim of this paper is to analyze the determinants of the survival of German manufacturing establishments devoting special interest to the multi-dimension approach, thus investigating business-, industry-, and region-specific survival determinants. By using a micro-panel data set of all German manufacturing establishments for the period 1992 to 2005, we employ both non-parametric and semi-parametric procedures that are specifically designed to analyze duration phenomena in order to ascertain survival determinants by explaining the time period between a firm's start-up and its cessation of economic activity. The results enable us to give advice on how to improve the survival conditions of businesses in certain regions and industries and, thus, to enhance the number of establishments with the potential to contribute to regional employment. The main findings indicate that the probability of exit is higher for very young and rather old businesses and also for relatively small businesses. Besides the overall finding of a higher exit risk in agglomerated areas, an above-average level of highly qualified employees working in the establishments decreases the probability of exit. Accordingly, businesses in R&D intensive or high-tech industries enjoy better survival prospects than businesses in other industries. Moreover, we find evidence that that regional industry specialization is not beneficial for the survival of newcomers in a respective industry. This result adds some interesting points to the findings of Dumais, Ellison and Glaeser (2002) who discovered that closure is less likely in those regions that belong to the current geographic centers of an industry and tends to increase geographic concentration. Our results suggest that in German manufacturing industries not only a business' entry but also its survival chances (in opposition to closure in general) are forces that reduce geographic concentration. Possible benefits from geographically bounded, within-industry spillovers seem to be of less importance than the counterforce of intensified local competition for survival.
Keywords: C41; L25; L26; L60; 330; New firm survival; hazard rates; duration analysis; entrepreneurship